2019
DOI: 10.1177/1756286419833478
|View full text |Cite
|
Sign up to set email alerts
|

Human induced pluripotent stem cell models for the study and treatment of Duchenne and Becker muscular dystrophies

Abstract: Duchenne and Becker muscular dystrophies are the most common muscle diseases and are both currently incurable. They are caused by mutations in the dystrophin gene, which lead to the absence or reduction/truncation of the encoded protein, with progressive muscle degeneration that clinically manifests in muscle weakness, cardiac and respiratory involvement and early death. The limits of animal models to exactly reproduce human muscle disease and to predict clinically relevant treatment effects has prompted the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
33
0
9

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(42 citation statements)
references
References 155 publications
(344 reference statements)
0
33
0
9
Order By: Relevance
“…For instance, CRISPR can be used to generate desired patient mutations in control hiPSC lines, providing unprecedented versatility in modeling a great number of DMD mutations in vitro. iCMs have the added advantage of more capably modeling the human heart in terms of physiology [62,89]. Differences in ion channels responsible for repolarization, as well as in the localization of sarcomeric proteins exist between mouse and human hearts, to name a few.…”
Section: Studies Using Human Ipsc Modelsmentioning
confidence: 99%
“…For instance, CRISPR can be used to generate desired patient mutations in control hiPSC lines, providing unprecedented versatility in modeling a great number of DMD mutations in vitro. iCMs have the added advantage of more capably modeling the human heart in terms of physiology [62,89]. Differences in ion channels responsible for repolarization, as well as in the localization of sarcomeric proteins exist between mouse and human hearts, to name a few.…”
Section: Studies Using Human Ipsc Modelsmentioning
confidence: 99%
“…Theoretically, the potential of iPSCs is based on their capacity to differentiate virtually to any cell type, but in practice, the reality is rather different. It is frequent that the differentiation gives rise to an undesirable phenotypic heterogeneity and a lack of maturity, with low-efficiency rates [95]. In terms of iPSCs differentiation, there are several distinct approaches that could be implemented.…”
Section: Loose Ends In the Clinical Ipscs Applicationmentioning
confidence: 99%
“…For instance, CRISPR can be used to generate desired patient mutations in control hiPSC lines, providing unprecedented versatility in modeling a great number of DMD mutations in vitro. iCMs have the added advantage of more capably modeling the human heart in terms of physiology [64,91]. Differences in ion channels responsible for repolarization, as well as in the localization of sarcomeric proteins exist between mouse and human hearts, to name a few.…”
Section: Studies Using Human Ipsc Modelsmentioning
confidence: 99%
“…Methods for standardizing the reprogramming and differentiation of hiPSCs are currently being optimized to address these issues. Second, iCMs actually exhibit limited maturation [64,91,102]. In fact, it has been shown that iCMs are more similar to fetal than adult cardiomyocytes, and thus may not faithfully recapitulate all disease phenotypes.…”
Section: Studies Using Human Ipsc Modelsmentioning
confidence: 99%
See 1 more Smart Citation